Analysis of Consistency in Planning and Budgeting: The Case in Purbalingga Regency - Bayu Kharisma; Sutyastie S. Remi; Alfian Massagony; Al Fitra Ramadhan (LPPM Universitas BSI, 2021)
Consistency of planning and budgeting plays an important role in supporting the government to achieve its strategic objectives and is an important instrument to improve the quality of human development and the welfare of the community. Infrastructure development will open economic access and accelerate the added value of the people's economy. Purbalingga Regional Government through its planning document sets out a development plan to improve infrastructure in the region. The purpose of this research is to analyze the consistency between planning and budgeting in Purbalingga Local Government. The results showed that in general the level of consistency between planning and regional budgeting is relatively good, but the results obtained can not be separated from various shortcomings, where there are still many activities that are not aligned. Some of the things that can be done by the government are increasing the capacity of the team planning apparatus, increasing the role of the regional inspectorate, and increasing the government's commitment in maintaining consistency of planning and budgeting. Keywords: planning, budgeting, consistency, infrastructure